Partial cutting in a dry temperate forest ecosystem alleviates growth loss under drought - Montwé, David; Isaac-Renton, Miriam; Standish, Audrey; Axelson, Jodi (Frontiers in Forests and Global Change, 2022)
The increasing frequency of severe drought and heat events under climate change is a major cause for concern for forest productivity and survival. One potential solution to improve forest resilience to drought may involve tree removal to reduce competition. To quantify potential benefits of partial cutting systems under drought, we use tree-ring data from a long-term partial cutting experiment in a dry ecosystem in western Canada, composed primarily of mature interior Douglas-fir (Pseudotsuga menziesii var. glauca). We ask: (1) How does tree removal change growth responses to drought and (2) how persistent are effects across multiple drought events? We compare growth responses in 83 trees up to 400 years in age from eight treatment units in a randomized experimental design representing a logging treatment with 25% basal area retention and a control (100% basal area retention). Retention harvesting was conducted in winter of 2002/2003 after a moderate drought in the summer of 2002. The site experienced a more severe drought in 2009 and a drought-heat event in 2015. In 2020, we obtained tree height and diameter data as well as tree increment cores from canopy dominant Douglas-fir, which were used to derive basal area increments. Based on these growth increments, we calculated four indices of resilience to drought. Growth increments of remaining individuals substantially increased after tree removal. Relative to the control, the low retention treatment expressed significantly higher post-drought growth increments compared to growth increments after the drought years of 2002 and 2009, i.e., higher drought recovery. Growth increments in the low retention treatment also had a significantly higher ability to regain pre-drought growth levels after the 2002 and 2009 droughts, i.e., higher drought resilience. However, the treatment did not show higher resilience under a heat-drought event in 2015. Although the treatment effects on drought response indices diminished over time, the absolute growth increments of residual trees remained higher than the control 17 years after harvest, despite repeated droughts. These results suggest that partial cutting on moisture-limited sites provides immediate and medium term benefits for remaining trees in terms of drought resilience, which may help forests adapt to climate change.